Step
*
1
2
1
2
1
1
of Lemma
permutation-sign-flip-adjacent
1. n : ℕ
2. f : {f:ℕn ⟶ ℕn| Inj(ℕn;ℕn;f)} 
3. u : ℕn - 1
4. v : ℤ
5. sign((f (u + 1)) - f u) = v ∈ ℤ
6. v1 : ℤ
7. sign((f u) - f (u + 1)) = v1 ∈ ℤ
8. (v * v1) = (-1) ∈ ℤ
9. ∀[f:ℕn ⟶ ℤ]. (Π(f[x] | x < n) = (Π(if (x =z u) then 1 else f[x] fi  | x < n) * f[u]) ∈ ℤ)
10. ∀[f:ℕn ⟶ ℤ]. (Π(f[x] | x < n) = (Π(if (x =z u + 1) then 1 else f[x] fi  | x < n) * f[u + 1]) ∈ ℤ)
⊢ ((Π(if (j =z u + 1) then 1
    if (j =z u) then 1
    if (j =z u) then Π(sign((f (u + 1)) - f i) | i < u + 1) * v
    if (j =z u + 1) then Π(sign((f u) - f i) | i < u + 1) * v1
    else Π(sign((f j) - f i) | i < j)
    fi  | j < n)
   * Π(sign((f u) - f i) | i < u + 1)
   * v1)
* Π(sign((f (u + 1)) - f i) | i < u + 1)
* v)
= (-((Π(if (j =z u + 1) then 1
  if (j =z u) then 1
  else Π(sign((f j) - f i) | i < j)
  fi  | j < n)
  * Π(sign((f (u + 1)) - f i) | i < u + 1))
  * Π(sign((f u) - f i) | i < u)))
∈ ℤ
BY
{ (Subst' Π(if (j =z u + 1) then 1
   if (j =z u) then 1
   if (j =z u) then Π(sign((f (u + 1)) - f i) | i < u + 1) * v
   if (j =z u + 1) then Π(sign((f u) - f i) | i < u + 1) * v1
   else Π(sign((f j) - f i) | i < j)
   fi  | j < n)
   = Π(if (j =z u + 1) then 1
     if (j =z u) then 1
     else Π(sign((f j) - f i) | i < j)
     fi  | j < n)
   ∈ ℤ 0
   THENA (EqCDA THEN AutoSplit)
   ) }
1
1. n : ℕ
2. f : {f:ℕn ⟶ ℕn| Inj(ℕn;ℕn;f)} 
3. u : ℕn - 1
4. v : ℤ
5. sign((f (u + 1)) - f u) = v ∈ ℤ
6. v1 : ℤ
7. sign((f u) - f (u + 1)) = v1 ∈ ℤ
8. (v * v1) = (-1) ∈ ℤ
9. ∀[f:ℕn ⟶ ℤ]. (Π(f[x] | x < n) = (Π(if (x =z u) then 1 else f[x] fi  | x < n) * f[u]) ∈ ℤ)
10. ∀[f:ℕn ⟶ ℤ]. (Π(f[x] | x < n) = (Π(if (x =z u + 1) then 1 else f[x] fi  | x < n) * f[u + 1]) ∈ ℤ)
⊢ ((Π(if (j =z u + 1) then 1
    if (j =z u) then 1
    else Π(sign((f j) - f i) | i < j)
    fi  | j < n)
   * Π(sign((f u) - f i) | i < u + 1)
   * v1)
* Π(sign((f (u + 1)) - f i) | i < u + 1)
* v)
= (-((Π(if (j =z u + 1) then 1
  if (j =z u) then 1
  else Π(sign((f j) - f i) | i < j)
  fi  | j < n)
  * Π(sign((f (u + 1)) - f i) | i < u + 1))
  * Π(sign((f u) - f i) | i < u)))
∈ ℤ
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  f  :  \{f:\mBbbN{}n  {}\mrightarrow{}  \mBbbN{}n|  Inj(\mBbbN{}n;\mBbbN{}n;f)\} 
3.  u  :  \mBbbN{}n  -  1
4.  v  :  \mBbbZ{}
5.  sign((f  (u  +  1))  -  f  u)  =  v
6.  v1  :  \mBbbZ{}
7.  sign((f  u)  -  f  (u  +  1))  =  v1
8.  (v  *  v1)  =  (-1)
9.  \mforall{}[f:\mBbbN{}n  {}\mrightarrow{}  \mBbbZ{}].  (\mPi{}(f[x]  |  x  <  n)  =  (\mPi{}(if  (x  =\msubz{}  u)  then  1  else  f[x]  fi    |  x  <  n)  *  f[u]))
10.  \mforall{}[f:\mBbbN{}n  {}\mrightarrow{}  \mBbbZ{}].  (\mPi{}(f[x]  |  x  <  n)  =  (\mPi{}(if  (x  =\msubz{}  u  +  1)  then  1  else  f[x]  fi    |  x  <  n)  *  f[u  +  1]))
\mvdash{}  ((\mPi{}(if  (j  =\msubz{}  u  +  1)  then  1
        if  (j  =\msubz{}  u)  then  1
        if  (j  =\msubz{}  u)  then  \mPi{}(sign((f  (u  +  1))  -  f  i)  |  i  <  u  +  1)  *  v
        if  (j  =\msubz{}  u  +  1)  then  \mPi{}(sign((f  u)  -  f  i)  |  i  <  u  +  1)  *  v1
        else  \mPi{}(sign((f  j)  -  f  i)  |  i  <  j)
        fi    |  j  <  n)
      *  \mPi{}(sign((f  u)  -  f  i)  |  i  <  u  +  1)
      *  v1)
*  \mPi{}(sign((f  (u  +  1))  -  f  i)  |  i  <  u  +  1)
*  v)
=  (-((\mPi{}(if  (j  =\msubz{}  u  +  1)  then  1
    if  (j  =\msubz{}  u)  then  1
    else  \mPi{}(sign((f  j)  -  f  i)  |  i  <  j)
    fi    |  j  <  n)
    *  \mPi{}(sign((f  (u  +  1))  -  f  i)  |  i  <  u  +  1))
    *  \mPi{}(sign((f  u)  -  f  i)  |  i  <  u)))
By
Latex:
(Subst'  \mPi{}(if  (j  =\msubz{}  u  +  1)  then  1
  if  (j  =\msubz{}  u)  then  1
  if  (j  =\msubz{}  u)  then  \mPi{}(sign((f  (u  +  1))  -  f  i)  |  i  <  u  +  1)  *  v
  if  (j  =\msubz{}  u  +  1)  then  \mPi{}(sign((f  u)  -  f  i)  |  i  <  u  +  1)  *  v1
  else  \mPi{}(sign((f  j)  -  f  i)  |  i  <  j)
  fi    |  j  <  n)
  =  \mPi{}(if  (j  =\msubz{}  u  +  1)  then  1
      if  (j  =\msubz{}  u)  then  1
      else  \mPi{}(sign((f  j)  -  f  i)  |  i  <  j)
      fi    |  j  <  n)  0
  THENA  (EqCDA  THEN  AutoSplit)
  )
Home
Index